INTEGRATION OF NATIONAL AND MODERN TECHNOLOGIES IN EDUCATIONAL PROCESSES - Sokhibidavron MELIYEV (Scholar Express Journal, 2024)
In this article, the scientific basis of national and modern technologies in the educational process is presented, practical efforts to integrate these technologies are thoroughly reviewed by the author, and the national and foreign experience in the training of highly qualified personnel is widely covered. The article also shows the main features that determine the quality of the educational process in the training of highly qualified personnel, as well as the rules that represent the basis of the concept of the quality system in a higher educational institution.
Keywords: Education; Educationmanagement; globalization